The Communication between Students and Teachers…: Barriers and the Ways to Overcome them - Boltá Hidalgo, María (Annales Universitatis Paedagogicae Cracoviensis. Studia ad Didacticam Scientiarum Socialium Pertinentia, 2020)
The purpose of this article is to explain some of the barriers that teachers can face when they are trying to communicate with their students. At the same time we will suggest some ideas to overcome them, as well as examples of different situations experienced by teachers. Also, there are some cases where we can even use these barriers as a way to improve the learning process. More specifically, we are going to focus on cultural barriers and psychological barriers. Another topic that we will be focusing on is the digital generation and how these differences can generate a new type of barrier.